A Theoretical Study on the use of Passive Soil Resistance in Winch Anchor Design - Ahmad, Desa (1983)
This paper describes work being carried out to determine the length and depth of a cutting blade required to support a rescue vehicle fitted with a winch. Analytical work described relates mostly to the suitability of blade used. The design was confined to the case of the wide cutting blade moving in a direction perpendicular to the breadth of the blade because of its two dimensional simplicity. The approach adopted was based on a method already presented for the rapid calculation of passive soil resistance on a plane wide structure extending to the soil surface and having any rake angle as well as a wide range of directions of interface motion.